Towards a Critical Anthology of Pre-Modern Bosom Serpent Folklore. Issue 3 (1st September 2016) - Ermacora, Davide; Labanti, Roberto; Marcon, Andrea
Abstract: We present a preview of our work for a critical anthology of medieval and pre-medieval fantastic folklore narratives about animals in the human body. These are generally referred to among English-speaking scholars as 'bosom serpent' legends. In particular, we provide here two of the most ancient texts from the section of the anthology on medieval Scandinavia. We also offer two little-known narratives, a medieval Latin saint's life and one from the Byzantine Greek world.